Carob Kibble: A Bioactive-Rich Food Ingredient - Nasar-Abbas, S.; e-Huma, Z.; Vu, T.; Khan, M.; Esbenshade, H.; Jayasena, Vijay (2016)
© 2015 Institute of Food Technologists®. Carob (Ceratonia siliqua L.) is well known for its valuable locust bean gum obtained from the carob seeds. Separation of seeds from the pod leaves behind the carob kibble which is a good source of dietary fiber, sugars, and a range of bioactive compounds such as polyphenols and pinitol. Bioactive compounds present in carob kibble have been found to be beneficial in the control of many health problems such as diabetes, heart diseases, and colon cancer due to their antidiabetic, antioxidant, and anti-inflammatory activities. Carob kibble has substantial potential to be used as a food ingredient. This article focuses on the composition, health benefits, and food applications of carob kibble.